Light and Electron Microscopy of Bone Marrow Hemopoiesis in Late Embryonal and Early Postnatal Mice: A Qualitative and Quantitative Study - ITO, Takashi; MATSUMURA, George; SASAKI, Kazunobu (Archivum histologicum japonicum, 1984)
Using serial sections of the entire body of late embryonal and early postnatal mice, a morphologic analysis of the bone marrow in the whole skeleton was made qualitatively and quantitatively. Hemopoietic cells in the developing marrow were also examined at the light and electron microscopic levels. Before birth, the bone marrow is quite small in volume. During the first five postnatal days, the marrow shows an approximately 65-fold increase in total volume. At 0-3 days of age, hemopoiesis begins in the marrow throughout the body. Marrow hemopoiesis starts earlier in the rib, scapula, humerus and femur. The development of hemopoiesis proceeds through the following three stages: 1) formation of the marrow cavity, 2) accumulation of neutrophils in the cavity, and 3) appearance of hemopoietic cells. In the bone marrow prior to active hemopoiesis, a majority of cells first appearing are mature neutrophils, among which immature erythroblasts and dark small lymphocytes, although very small in number, are seen. The functional significance of the cells appearing early is discussed in relation to the sequent events involved in marrow hemopoiesis. In addition to the marrow, development of the other blood forming tissues and lymphatic organs is also examined quantitative-morphologically.